Ocular morbidity among primary school children - Sherpa, D (Journal of Chitwan Medical College, 2014)
Knowledge of disease pattern in children can help design preventive and curative strategies. This study is conducted to determine the pattern of ocular morbidity among the primary school children. Children of primary school were included in this study. A complete eye examination was done in all children including loupe examination, refraction and Perkins tonometry. funduscopy were done in selected children. A total of 332 primary school children were included in the study, of which 332 children 99 (29.82 %) had ocular morbidity. Refractive error was the commonest type of ocular morbidity in 31 (9.33 %). Myopia was the commonest type of refractive error (84.77%) in contrast to hypermetropia (0.30 %). 27. Conjunctivitis was the second common type of ocular morbidity (17%). Among others, Convergence insufficiency in 17 children (5.12%), exodeviation in 10 children (3.01%), blepharitis in 5 children (1.5%), vitamin A deficiency in 5 children (1.50%), ocular trauma in 2 patients (0.60%) and stye in 2 children (0.60%) were found. Refractive error is the commonest form of ocular morbidity in primary school children. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10860 Journal of Chitwan Medical College 2014; 4(2): 32-34